2003
DOI: 10.1074/jbc.m306344200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Escherichia coli PdxA, an Enzyme Involved in the Pyridoxal Phosphate Biosynthesis Pathway

Abstract: Pyridoxal 5-phosphate is an essential cofactor for many enzymes responsible for the metabolic conversions of amino acids. Two pathways for its de novo synthesis are known. The pathway utilized by Escherichia coli consists of six enzymatic steps catalyzed by six different enzymes. The fourth step is catalyzed by 4-hydroxythreonine-4-phosphate dehydrogenase (PdxA, E.C. 1.1.1.262), which converts 4-hydroxy-L-threonine phosphate (HTP) to 3-amino-2-oxopropyl phosphate. This divalent metal ion-dependent enzyme has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…YaaE is an α/β three layer sandwich containing twelve β-strands, six α-helices and three 3 10 helices ( Figure 1c) and is characteristic of class I amidotransferases. The structure of YaaE in complex with YaaD is similar to the structures of YaaE from B. subtilis (17), YaaE from B. stearothermophilus (PDB ID 1Q7R) and Pdx2 from P. falciparum (26).…”
Section: Structure Of the Yaad/yaae Protomermentioning
confidence: 99%
See 2 more Smart Citations
“…YaaE is an α/β three layer sandwich containing twelve β-strands, six α-helices and three 3 10 helices ( Figure 1c) and is characteristic of class I amidotransferases. The structure of YaaE in complex with YaaD is similar to the structures of YaaE from B. subtilis (17), YaaE from B. stearothermophilus (PDB ID 1Q7R) and Pdx2 from P. falciparum (26).…”
Section: Structure Of the Yaad/yaae Protomermentioning
confidence: 99%
“…Helix α0 is involved in extensive interactions with YaaE and helps form one side of the proposed ammonia channel. Comparing YaaD to PdxS, a series of smaller conformational changes in the 3 10 -helix (237-240), the β6-α6 loop, α8 and α8a connect adjacent active sites within the PLP synthase complex. In the structure of YaaD residues 46-56 form an active site loop.…”
Section: Conformational Changes Upon Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In many bacteria and plants, PLP is synthesized by a de novo pathway, but most cells rely on a nutritional source of vitamin B 6 , i.e., pyridoxine (PN), pyridoxal (PL), or pyridoxamine (PM) (18). All cells, however, have a salvage pathway for reutilizing the PLP that is liberated during protein turnover (21).…”
mentioning
confidence: 99%
“…The SSN for the PdxA family filtered with an alignment score of 80 (∼47% sequence identity) revealed that the members that are encoded genome proximal to DUF1537 proteins (designated a PdxA2 subgroup) are separated from the proteins (PdxA) that catalyze the NAD(P) + -dependent oxidative decarboxylation of 4-hydroxy-L-threonine 4-phosphate (4HT-4P) to form 3-amino-1-hydroxyacetone 1-phosphate in the biosynthetic pathway for pyridoxal 5′-phosphate (PLP) (SI Appendix, Fig. S5) (26,27), suggesting a distinct function.…”
Section: Synergistic Analysis Of Ssns and Gnns Enables The Predictionmentioning
confidence: 99%